Development of 1-N-(11)C-Methyl-l- and -d-Tryptophan for pharmacokinetic imaging of the immune checkpoint inhibitor 1-Methyl-Tryptophan - Xie, Lin (Sci Rep, 2015)
1-Methyl-tryptophan (1MTrp) is known as a specific inhibitor targeting the immune- checkpoint protein indoleamine-2,3-dioxygenase, in two stereoisomers of levorotary (l) and dextrorotary (d). A long-standing debate exists in immunology and oncology: which stereoisomer has the potential of antitumor immunotherapy. Herein, we developed two novel radioprobes, 1-N-(11)C-methyl-l- and -d-tryptophan ((11)C-l-1MTrp and (11)C-d-1MTrp), without modifying the chemical structures of the two isomers, and investigated their utility for pharmacokinetic imaging of the whole body. (11)C-l-1MTrp and (11)C-d-1MTrp were synthesized rapidly with radiochemical yields of 47 ± 6.3% (decay-corrected, based on (11)C-CO(2)), a radiochemical purity of >98%, specific activity of 47–130 GBq/μmol, and high enantiomeric purity. PET/CT imaging in rats revealed that for (11)C-l-1MTrp, the highest distribution of radioactivity was observed in the pancreas, while for (11)C-D-1MTrp, it was observed in the kidney. Ex vivo biodistribution confirmed the PET/CT results, indicating the differences in pharmacokinetics between the two isomers. Both (11)C-l-1MTrp and (11)C-d-1MTrp are therefore useful PET probes for delineating the distribution and action of the checkpoint inhibitor 1MTrp in vivo. This study represents the first step toward using whole-body and real-time insight to disentangle the antitumor potential of the two stereoisomers of 1MTrp, and it can facilitate the development of 1MTrp immunotherapy.